1992
DOI: 10.1165/ajrcmb/7.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Human Lung Mast Cells and Pulmonary Macrophages Produce Tumor Necrosis Factor-α in Sensitized Lung Tissue after IgE Receptor Triggering

Abstract: Tumor necrosis factor (TNF) is considered to play a key role in the pathogenesis of allergic disorders. We examined TNF production in human lung fragments after IgE receptor triggering at mRNA and protein levels. IgE receptor triggering was performed by sensitizing lung fragments with monoclonal human IgE and then exposing them to anti-human IgE antibody. Cytotoxic activity against L929 cells appeared in the culture supernatant of lung fragments 2 h after IgE receptor triggering and increased for up to 4 h. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(69 citation statements)
references
References 19 publications
3
65
0
1
Order By: Relevance
“…TNF-α is a multifunctional proinflammatory TH 1 cytokine which has been suggested to play a critical role in the initiation, maintenance and progression of airway inflammation in asthma. TNF-α is stored in granules and is known to be released during allergic responses both from mast cells and macrophages via Ig-E dependant mechanisms 34 . Many other cell types that play a contributing role in the pathogenesis of asthma are also significant sources of TNF-α, including eosionphils 35 , epithelial cells 36 and T cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α is a multifunctional proinflammatory TH 1 cytokine which has been suggested to play a critical role in the initiation, maintenance and progression of airway inflammation in asthma. TNF-α is stored in granules and is known to be released during allergic responses both from mast cells and macrophages via Ig-E dependant mechanisms 34 . Many other cell types that play a contributing role in the pathogenesis of asthma are also significant sources of TNF-α, including eosionphils 35 , epithelial cells 36 and T cells 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Observations that TNF-α is released via the IgE-dependent activation of mast cells (Gordon et al, 1990) or in the sensitized human lung (Ohkawara et al, 1992) suggest that TNF-α contributes to the allergen-induced inflammatory response. Amrani et al (1995) showed that exposure of human airway smooth muscle cells to TNF-α for 24 hr potentiates the increase in cytosolic free calcium induced by contractile agonists such as carbachol and bradykinin.…”
Section: Discussionmentioning
confidence: 99%
“…Much higher levels of exhaled CO and NO during the late asthmatic reaction may also be due to HO-1 activation by inflammatory cytokines such as interleukin (IL)-1, IL-6, tumour necrosis factor (TNF-a) [32,33] and iNOS activation by IL-1 and TNF-a [34,35] which are abundant in BAL at the time of the late asthmatic reaction [36,37]. Increased production of oxidants by incoming inflammatory cells and tissue cells may contribute to HO-1 activation [38], explaining higher CO levels in dual responders than in single responders.…”
Section: Discussionmentioning
confidence: 99%